Raising the crossbar: power politics and the role values and self-interest in sport - Labuschagne, Pieter (Faculty of Humanities, University of the Free State, 2013)
Within the broader ambit of sport the organisation and administration of athletics have been underpinned or driven by strong opposing undercurrents such as self-interests and basic values such as fairness and equality. In the South African context power politics and the interference of central government in sport followed a strong self-interest in sport, which translated into regulatory policies which resulted in the isolation of most sports codes from international participation. In the article the path of athletics in South Africa is recounted as an example of a sports code that has been dictated and dominated by the two approaches to sport – the emphasis on how the self-interest displayed by the South African National Party led government translated into the isolation of South Africa in the sport of athletics on the world stage. However, during democratic normalisation in the country a strong value driven approach was adopted which paved the way for South Africa back into the fold of international sport. Unfortunately, at the same time, in a climate of commercialisation and self-interest, sports administrators of the International Olympic Committee (IOC) and International Amateur Athletics Federation (IAAF) delayed the re-entry of South Africa into international sport for more than a year.
Keywords: Power politics; Values; Self-interest; Athletics; Olympic Games; International Olympic Committee